Highly Efficient (110) Orientated FA‐MA Mixed Cation Perovskite Solar Cells via Functionalized Carbon Nanotube and Methylammonium Chloride Additive. Issue 5 (18th September 2019) - Wang, Yong; Li, Wei; Zhang, Taiyang; Li, Donghui; Kan, Miao; Wang, Xingtao; Liu, Xiaomin; Wang, Tao; Zhao, Yixin
Abstract: High‐quality perovskite thin film with few defects/traps is the key to assemble high‐performance perovskite solar cells (PSCs). Because of the high defects/traps density in polycrystalline perovskite films and challenging fabrication of single crystal devices, the polycrystalline perovskite films consisting of the oriented quasi‐single crystals with reduced defect density are the ideal compromise. In this work, the fabrication of highly crystalline uniaxial‐orientated perovskite thin films is demonstrated, with enhanced charge‐carrier transport through amino‐functionalized carbon nanotube (CNT‐NH2 ) and methylammonium chloride (MACl) additive. X‐ray scattering, including synchrotron‐based grazing incidence wide‐angle X‐ray scattering, reveal that the MA0.85 FA0.15 PbI3 thin films grown with the assistance of both CNT‐NH2 and MACl additives exhibit strong (110) orientation. Because of the highly crystallinity, uniaxial‐orientation, and large crystal grain size, the FA‐MA mixed cation perovskite films exhibit improved charge‐carrier dynamics to facilitate charge extraction and transport. The champion PSC device based on these perovskite films achieves power conversation efficiency of 21.05%. This work provides a general approach for preparing high crystalline uniaxial‐orientated perovskite films with enhanced charge‐carrier transport for various optoelectronic applications. Abstract : The highly crystalline uniaxial‐orientated FA‐MA mixed cation perovskite films, fabricated by amino‐functionalized carbon nanotube (CNT‐NH2 ) and methylammonium chloride additive, exhibit improved charge‐carrier dynamics to facilitate charge extraction and transport. The champion device based on the uniaxial‐orientated MA0.85 FA0.15 PbI3 films with optimal amino‐functionalized CNT‐NH2 content exhibits efficiency of 21.05%.